2000
DOI: 10.1046/j.1365-201x.2000.00663.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of AVP-V2 receptor stimulation on local GFR in the rat kidney

Abstract: The effect of AVP-V2 receptor agonist desmopressin, dDAVP, its non-peptide antagonist OPC-31260 and vehicle infusion on glomerular filtration rate (GFR) in the outer, middle and inner cortex was studied in both hydropenic and water diuretic Inactin anaesthetized female Sprague-Dawley rats using the aprotinin method. Two subsequent GFR measurements were carried out in the same kidney by injection of 125I- and 131I-labelled aprotinin before and after i.v. infusion of dDAVP, OPC-31260 or the vehicle. Acute infusi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
18
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 0 publications
1
18
0
Order By: Relevance
“…In parallel with V 2 R expression, we found high-level baseline signals of phosphorylated NKCC2 in macula densa across species, suggesting that AVP may influence tubuloglomerular signaling via modulation of NKCC2-dependent transpepithelial transport. This observation may be related to AVP-dependent acute changes in glomerular filtration rate in rat kidney (4,37). However, the detection of selectively high phosphorylated NKCC2 immunoreactivity in DI rat macula densa underscores AVP-independent, constitutive activation of the cotransporter at this site.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…In parallel with V 2 R expression, we found high-level baseline signals of phosphorylated NKCC2 in macula densa across species, suggesting that AVP may influence tubuloglomerular signaling via modulation of NKCC2-dependent transpepithelial transport. This observation may be related to AVP-dependent acute changes in glomerular filtration rate in rat kidney (4,37). However, the detection of selectively high phosphorylated NKCC2 immunoreactivity in DI rat macula densa underscores AVP-independent, constitutive activation of the cotransporter at this site.…”
Section: Discussionmentioning
confidence: 68%
“…These studies showed solid V 2 R expression in the CD, with some reference to regional differences in intensity believed to reflect AVPinduced effects on the stimulation/insertion of AQP-2 and urea transporter(s) (4,28,36). Localization of V 2 R was further reported in rat kidney TAL (10,39) and macula densa (32); binding of oxytocin, which is structurally related to AVP, and expression of oxytocin receptor in macula densa as well (33,45) support a role for AVP and, possibly, oxytocin in the regulation of glomerular filtration rate (37). A recent study analyzing V 2 R distribution in mouse and human kidney confirmed V 2 R expression in CD, but not in TAL (9).…”
mentioning
confidence: 99%
“…These effects are further supported by our findings that SR 49059 slightly improved GFR in CHF rats but not in sham controls rats 60 min after the drug administration. Moreover, by acting through V 1a , AVP causes contraction, proliferation, and hypertrophy of the mesangial cells, leading to decrease in GFR and ultrafiltration coefficient (Ganz et al, 1988;Roald et al, 2004). Taken together, the adverse renal and systemic effects of AVP mediated via V 1a may attenuate the diuretic action of SR 121463B in CHF by diverting the binding of the hormone selectively toward V 1a receptors.…”
mentioning
confidence: 92%
“…VP has been implicated in the elevation of GFR in rats (Bouby et al, 1996;Roald et al, 2000), so we hypothesized that creatinine excretion would increase in response to acutely elevated [VP]. Although the net effect was no significant change in GFR following infusion of VP, the significant increase in plasma U:C ratio, a recognized indicator of altered filtration rate (Duarte and Preuss, 1993), suggests that filtration rate may have been acutely elevated as a consequence of the increase in [VP].…”
Section: Table·1 Fractional Excretion Of Electrolytes and Urea Over mentioning
confidence: 99%
“…Aside from its role in tubular resorption of water, VP has also been implicated in elevating glomerular filtration rate (GFR) in rats (Bouby et al, 1996;Roald et al, 2000) and Na + excretion in dogs (Bie et al, 1984;Buckalew and Dimond, 1976;Chan and Sawyer, 1961;Johnson et al, 1979;Kompanowska-Jezierska et al, 1998;Smith et al, 1979;Sondeen and Claybaugh, 1989). Although infusion of hypertonic saline in fasting northern elephant seal pups induced a chronic (24·h) elevation in plasma [VP], GFR and Na + excretion, the contribution of elevated [VP] to an increase in GFR and Na + excretion could not be ascertained (Ortiz et al, 2002b).…”
mentioning
confidence: 99%